Analisis Kualitas Pelayanan UGD Puskesmas Woha Kabupaten Bima terhadap Pengguna Kartu BPJS - Nurmiftahul Abrar; Gery Katon Mahendra (Wacana Publik, 2022)
The purpose of this study was to determine the service quality of the Woha Health Center Emergency Unit, Bima Regency for BPJS Card users. by using the mix method. The results of the research on the quality of the services of the Emergency Unit on the results of the research on the quality of the services of the Emergency Unit for BPJS card users at the Woha Health Center, Bima Regency, "Less Good" with a score of 66.5. (1) Equipment or facilities that are still incomplete, (2) Appearance/tidiness of employees in serving patients is good (3) Cleanliness and tidiness of the room is considered to be still not clean, (4) Services provided by health workers seem slow (5) Ease of handling the service process is not easy, patients have to go back and forth from home to take incomplete requirements, (6) the ability of officers to serve is good (7) The response of officers when responding to patient complaints is not good, there are still some officers who respond are still unsatisfactory to patients, (8) The staff's response to new patients is considered less (9) The attitude of the officers when serving is considered not good, (10) Are the officers friendly and polite enough still considered not good because there are still many officers who are not polite. practice, (11) Paying using a BPJS card whether the patient is considered not optimal by the respondent (12) The officer is always there when the patient receiving assistance is categorized as poor (13) The safety and comfort of the patient's bed is still not good (14) Ease of patient interaction with officers who are considered not good enough, and lastly (15) Ease of access for BPJS patients in service requests is considered poor by patients, the Emergency Room still lacks patient waiting chairs, bathroom fans/AC that needs to be there.